Pengukuran Pertumbuhan Volume Data pada Sistem Informasi Sekolah - Kurniawan, Muhammad Ramadhani; Sari, Waskita; Rohim, Hafi Amarta Afroni; Yaqin, Muhammad Ainul (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2020)
The School information system is a system that can streamline various school management processes with the available features. This school information system facilitates all aspects involved in estimating and school management. Growth (growth) is related to the problem of change in number and size. According to Hasan (2018), regression is a measuring tool that is also used to measure the correlation between variables. This paper describes in detail how to measure the growth in the volume of data available in schools. The measurement of data volume growth in school information systems consists of the complexity, number of transactions and size of the data. The three components are then processed through multiple linear regression and a multiple linear regression equation will be generated.